2010
DOI: 10.1007/s10562-010-0328-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxydehydrogenation of Ethane and Propane over Alkaline Metal Modified Fe-ZSM-5 Zeolites

Abstract: Iron modified zeolites of MFI structure, calcined at 873 and 1173 K, were doped with sodium cations in amounts corresponding to , , and to the total number of acidic centres, estimated from TPD of ammonia. Sodium modified Fe-ZSM-5(900) gradually lost their oxidative activity with an increase in the concentration of alkaline cations, while the activity of Na/Fe-ZSM-5(600) changed slightly and diminished considerably only after significant removal of acidic centres. The results of propane ODH reaction, performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…For the LT treatment, irrespective of the Si/Al ratio, three desorption peaks were observed for all the parent zeolites with their intensity decreasing with increasing Si/Al ratio. After the HT treatment a strong decrease of the peak at ~400 o C was observed for all zeolites which is consistent with a loss of Brønsted acid sites [10]. It is worth noting that the loss of acid sites has been thought to be due to partial dealumination [45]; however, from the XRD (not shown) and BET (Table 2) data little change following HT treatment is observed and, therefore, this is unlikely to be the cause in the present case.…”
Section: Dr-uv-vis Spectroscopysupporting
confidence: 73%
See 4 more Smart Citations
“…For the LT treatment, irrespective of the Si/Al ratio, three desorption peaks were observed for all the parent zeolites with their intensity decreasing with increasing Si/Al ratio. After the HT treatment a strong decrease of the peak at ~400 o C was observed for all zeolites which is consistent with a loss of Brønsted acid sites [10]. It is worth noting that the loss of acid sites has been thought to be due to partial dealumination [45]; however, from the XRD (not shown) and BET (Table 2) data little change following HT treatment is observed and, therefore, this is unlikely to be the cause in the present case.…”
Section: Dr-uv-vis Spectroscopysupporting
confidence: 73%
“…As stated in the introduction, this can be explained by the fact that only medium and weak acidic sites are responsible for the C-H bond activation, involved in oxidative dehydrogenation pathway [18,19]. This is supported by the work of Held et al who reported that the reduction of acid sites by means of high temperature treatment and sodium introduction, results in a clear decrease in selectivity to cracking products and CO 2 , while selectivity towards propene increased [10].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations